Is the decline in the information content of earnings following restatements temporary? - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2011)
Prior research finds that the decline in the information content of earnings after restatement announcements is temporary and that earnings response coefficient (ERC), the proxy for the information content of earnings, bounces back after three quarters. We find that this temporary decline documented in prior research is driven by two design choices: (1) the inclusion of both accounting irregularities and other restatements, and (2) the restriction of data availability for the two quarters immediately surrounding restatement announcements, which reduces the sample size by about half. After separately investigating accounting irregularities and other restatements and relaxing the data restriction, we find that accounting irregularity firms experience a significant decrease in ERC over a much longer period – close to three years after restatement announcements. In contrast, other restatement firms experience a decline in ERC only for one quarter after restatement announcements.